University-Company-State: Towards a Culture of Research and Innovation (2015)
The research book entitled University-Company-State: Towards a Culture of Research and Innovation aims at informing the academic community, the business sector, and the State, of the theoretical developments and practical experiences in the coordination between University-Company-State (UCS) resulting from processes of research, entrepreneur- ship, competitiveness, and innovation. All this occurs within the context of the Second Conference of Business Innovation and the relationship between the University-Company- State Committees (UCSC) of Cauca and Nariño, an open stage for establishing relationships among stakeholders from academia, the company, and the government, with the purpose of finding innovative processes that position regions locally and globally. This triadic relationship responds to the public policy on science, technology and innovation, and is key factor in the development of a globalized society, given that there is a correspondence between the capacity to generate knowledge with competitiveness and the economic and social development.The importance of this book lies in the relevance, appropriateness, and timeliness of the topic it deals with as it demands joint, inter-institutional and interdisciplinary work for betting on regional development. Furthermore, the conceptual basis, experiences, best practices and research results in the subject matter constitute a valuable contribution to support participation in the science, technology and innovation system. These elements create and consolidate a culture of research and innovation that boosts processes such as: First, identifying and defining the technological capacity of research groups and the building of a service portfolio through technological dossiers with the aim of reaching technological cooperation agreements; second, identifying and raising technological demand of the region's companies with the aim of gaining providers of creative solutions for existing problems; and third, coordinating supply and demand to optimize collective formulation of innovative projects.